Tinjauan Desain Website Kemlu.Go.Id - Widhyatmoko, Danu (Bina Nusantara University, 2013)
Review of kemlu.go.id website design is a research report on Kemlu.go.id website design. Kemlu.go.id website aims to be the information gateway of Ministry of Foreign Affairs, and also as guidelines of foreign politic policies of Republic of Indonesia. The review had been accomplished by using analytical method based on the